"Paying it forward": building a collective community for the community - Sahar, Rafidah (Sejahtera Centre for Sustainability and Humanity, 2023)
The idea of "paying it forward" has come up frequently in my personal and professional lives as a practitioner. Rather than merely navigating through life, I strongly believe that we are here to impact the world positively. My decision to teach Usrah in Action courses is driven by a deep desire to learn more about how I could contribute to society meaningfully and practically. I have witnessed the positive effects of tiny deeds of kindness on people, families, and even communities. I have seen the power of group effort in bringing about positive change in my past work with the local communities in Johor. Wanting to contribute more, education is my most effective instrument for enabling my students to make a difference in their own lives and the lives of others. Teaching the courses provides me the platform to assist my students in becoming active members of society and agents of change by equipping them with the information, abilities, and opportunities they need.